1996
DOI: 10.1073/pnas.93.26.15423
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-related species inhibit evoked neurotransmission but enhance spontaneous miniature synaptic currents in central neuronal cultures

Abstract: Nitric oxide (NO ⅐ ) does not react significantly with thiol groups under physiological conditions, whereas a variety of endogenous NO donor molecules facilitate rapid transfer to thiol of nitrosonium ion (NO ؉ , with one less electron than NO ⅐ ). Here, nitrosonium donors are shown to decrease the efficacy of evoked neurotransmission while increasing the frequency of spontaneous miniature excitatory postsynaptic currents (mEPSCs). In contrast, pure NO ⅐ donors have little effect (displaying at most only a sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…However, miniature and asynchronous release was greater in CIH rather than reduced. Directionally different results have been observed previously in which a decrease in evoked EPSP/EPSCs or endplate potentials is accompanied by increases or unaltered miniature events (Eliot et al, 1994;Zengel and Sosa, 1994;Cummings et al, 1996;Pan et al, 1996). We propose that the effects of CIH on the frequency of mEPSCs and aEPSCs versus the eEPSCs reflect differential regulation of release of two vesicular pools.…”
Section: Cih Modelsmentioning
confidence: 56%
“…However, miniature and asynchronous release was greater in CIH rather than reduced. Directionally different results have been observed previously in which a decrease in evoked EPSP/EPSCs or endplate potentials is accompanied by increases or unaltered miniature events (Eliot et al, 1994;Zengel and Sosa, 1994;Cummings et al, 1996;Pan et al, 1996). We propose that the effects of CIH on the frequency of mEPSCs and aEPSCs versus the eEPSCs reflect differential regulation of release of two vesicular pools.…”
Section: Cih Modelsmentioning
confidence: 56%
“…Moreover, photolysis of our caged NO affected NMDA but not non-NMDA receptor-mediated responses (see, for example, Fig. 3A and B) as predicted for the free radical (NO·) but not the nitrosonium (NO¤) species (Pan et al 1996). The mechanism by which NO depresses NMDA receptor function is not known, though redox modification of thiol groups associated with the receptor has been strongly implicated (Moriyoshi et al 1991;Lei et al 1992;Manzoni et al 1992;Lipton et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The multiplicity of actions reported for NO is likely to reflect the redox species involved. Compounds that evolve the free radical (NO·) have very little effect on non-NMDA receptor function, but compounds releasing nitrosonium ions (NO¤) reversibly depress synaptic transmission (Pan et al 1996). We are confident that our caged compound releases the free radical NO·, the form of NO produced by the enzymatic action of NOS (Garthwaite, 1991), on the basis of changes in the absorption spectrum of haemoglobin when exposed to photolytically released NO; these changes, reflecting the conversion of deoxyhaemoglobin to nitrosyl-haemoglobin, are stimulated by NO· but not by NO¤ (Bettache et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Different NO species formed in the spinal cord may be involved in the opposing actions of NO mentioned in the above studies. For instance, nitrosonium donors, but not pure NO donors, can alter synaptic neurotransmission (Pan et al, 1996). We have found that spinal NO interacts with L-cysteine to produce an antiallodynic effect through formation of S-nitrosothiols in a rat model of neuropathic pain (Chen et al, 2000).…”
Section: No Mediates the Effect Of Dpdpe On Dorsal Horn Neurons 1025mentioning
confidence: 93%